The Specific Role of Reactive Astrocytes in Stroke - Li, Leiyang; Zhou, Jinpeng; Han, Liying; Wu, Xun; Shi, Yingwu; Cui, Wenxing; Zhang, Shenghao; Hu, Qing; Wang, Jin; Bai, Hao; Liu, Haixiao; Guo, Wei; et al. (Frontiers in Cellular Neuroscience, 2022)
Astrocytes are essential in maintaining normal brain functions such as blood-brain barrier (BBB) homeostasis and synapse formation as the most abundant cell type in the central nervous system. After the stroke, astrocytes are known as reactive astrocytes (RAs) because they are stimulated by various damage-associated molecular patterns and cytokines, resulting in significant changes in their reactivity, gene expression, and functional characteristics. RAs perform multiple functions after stroke. The inflammatory response of reactive astrocytes may aggravate neuro-inflammation and release toxic factors to exert neurological damage. However, RAs also reduce excitotoxicity and release neurotrophies to promote neuroprotection. Furthermore, RAs contribute to angiogenesis and axonal remodeling to promote neurological recovery. Therefore, reactive astrocytes' biphasic roles and mechanisms make them an effective target for functional recovery after stroke. In this review, we summarized the dynamic functional changes and internal molecular mechanisms of reactive astrocytes after stroke, as well as their therapeutic potential and strategies, in order to comprehensively understand the role of reactive astrocytes in the outcome of stroke disease and provide a new direction for the clinical treatment of stroke.